2022
DOI: 10.1177/10499091211073328
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Palliative Care in Hospital Length of Stay and the Timing of Consultation

Abstract: Background Inpatient palliative care may reduce length-of-stay, costs, mortality, and prevent readmissions. Timing of consultation may influence outcomes. The aim of this study was to explore the timing of consultation and its influences patient outcomes. Method This retrospective study of hospital consultations between July 1, 2019 and December 31, 2019 compared patients seen within 72 hours of admission with those seen after 72 hours. Outcomes length of stay and mortality. Chi-square analyses for categorical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…There is evidence to support the cost-effectiveness of palliative care with regards to healthcare costs and the decrease in the utilization of aggressive treatments, including ventilation, endotracheal intubation, and resuscitation [11]. Other studies have indicated that patients who receive palliative care at the end of life will have lower hospitalization rates, fewer ICU days, less active treatment, and a reduced length of hospital stay (LOS) when they receive palliative consultations within 72 hours of being admitted to the hospital [12,13]. Nevertheless, the availability of medical resources can vary depending on the different diseases, clinical practices, and timing of palliative care interventions.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence to support the cost-effectiveness of palliative care with regards to healthcare costs and the decrease in the utilization of aggressive treatments, including ventilation, endotracheal intubation, and resuscitation [11]. Other studies have indicated that patients who receive palliative care at the end of life will have lower hospitalization rates, fewer ICU days, less active treatment, and a reduced length of hospital stay (LOS) when they receive palliative consultations within 72 hours of being admitted to the hospital [12,13]. Nevertheless, the availability of medical resources can vary depending on the different diseases, clinical practices, and timing of palliative care interventions.…”
Section: Introductionmentioning
confidence: 99%